2005
DOI: 10.2300/acari.14.1
|View full text |Cite
|
Sign up to set email alerts
|

Geographic Distribution of Neoseiulus longispinosus (Evans) and Its Habitat Plants in Thailand

Abstract: We studied the distribution of the predatory phytoseiid mite, Neoseiulus longispinosus (Evans), in Thailand. The predator was distributed over the entire areas of the country throughout the year. It was found on 33 plant species ranging from perennial plants such as fruit trees to annual crops such as vegetables and ornamentals. N. longispinosus was abundant on plants infested with spider mites producing heavy webbing on the lower surface of leaves.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 11 publications
0
7
0
1
Order By: Relevance
“…Neoseiulus longispinosus (Evans) is one of the most abundant and effective phytoseiids in Thailand and is commonly associated with many mite pests on crops of economic importance (Kongchuensin et al, 2005). Its role in suppressing populations of two-spotted spider mite, Tetranychus urticae Koch is evident on strawberry in northern Thailand (Kongchuensin et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Neoseiulus longispinosus (Evans) is one of the most abundant and effective phytoseiids in Thailand and is commonly associated with many mite pests on crops of economic importance (Kongchuensin et al, 2005). Its role in suppressing populations of two-spotted spider mite, Tetranychus urticae Koch is evident on strawberry in northern Thailand (Kongchuensin et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…In India, it has been observed to feed on Tetranychus species on apple and fig trees (Thakur & Dinabandhu, 2005). Kongchuensin et al (2005) reported it to prey on T. urticae on 33 plant species, including ornamentals, in Thailand. The biology of this predator was studied by Ho et al (1995).…”
Section: Discussionmentioning
confidence: 99%
“…N. longispinosus berhubungan dekat dengan Neoseiulus womersleyi (Schicha) secara biosistematika (Zhang 2003;Gerson et al 2003). Daerah sebar N. longispinosus meliputi Rusia, China, Jepang, Thailand, Australia, Hawai (Zhang 2003;Kongchuensin et al 2005), India, Taiwan, Filipina, Malaysia, Indonesia, dan Selandia Baru (Gerson et al (2003). N. longispinosus pertama kali dilaporkan dan ditemukan berasosiasi dengan Tetranychus bimaculatus Harvey pada tanaman ubi kayu di Indonesia (Evans 1952).…”
Section: N Longispinosus Termasuk Dalam Familiunclassified